The Baltic Sea Environment: an international satellite–mediated course. (4th August 2014) - Lindroos, P.; Modigh, R.; Ryden, L.
The satellite–mediated course The Baltic Sea Environment has reached about 6000 students in 80 universities in all countries surrounding the Baltic Sea. In ten sessions the course gave knowledge on basic facts and understanding of the causes of environmental decline in the Baltic region. The uniqueness of the present course is found in its regional application, in which the 13 countries in the region – the drainage area of the Baltic Sea – were connected into a borderless Baltic University. In the distribution of the satellite–mediated program both space–bridge sessions and conventionally televised sessions were used.